Independent effects of Src kinase and podoplanin on anchorage independent cell growth and migration. Issue 7 (26th April 2022) - Retzbach, Edward P.; Sheehan, Stephanie A.; Krishnan, Harini; Zheng, Haiyan; Zhao, Caifeng; Goldberg, Gary S.
Abstract: The Src tyrosine kinase is a strong tumor promotor. Over a century of research has elucidated fundamental mechanisms that drive its oncogenic potential. Src phosphorylates effector proteins to promote hallmarks of tumor progression. For example, Src associates with the Cas focal adhesion adaptor protein to promote anchorage independent cell growth. In addition, Src phosphorylates Cas to induce Pdpn expression to promote cell migration. Pdpn is a transmembrane receptor that can independently increase cell migration in the absence of oncogenic Src kinase activity. However, to our knowledge, effects of Src kinase activity on anchorage independent cell growth and migration have not been examined in the absence of Pdpn expression. Here, we analyzed the effects of an inducible Src kinase construct in knockout cells with and without exogenous Pdpn expression on cell morphology migration and anchorage independent growth. We report that Src promoted anchorage independent cell growth in the absence of Pdpn expression. In contrast, Src was not able to promote cell migration in the absence of Pdpn expression. In addition, continued Src kinase activity was required for cells to assume a transformed morphology since cells reverted to a nontransformed morphology upon cessation of Src kinase activity. We also used phosphoproteomic analysis to identify 28 proteins that are phosphorylated in Src transformed cells in a Pdpn dependent manner. Taken together, these data indicate that Src utilizes Pdpn to promote transformed cell growth and motility in complementary, but parallel, as opposed to serial, pathways.